Assessment of wheat genotypes for yield potential and stress adaptation - Kumar Jatav, Sunil; S Kandalkar, Vasant (Journal of Cereal Research, 2014)
Post-anthesis drought stress is the most important factor affecting wheat production adversely in dry-land area. In order to evaluate drought tolerance in bread wheat varieties, an experiment was conducted with 125 promising genotypes in randomized block design with two replications each in no-stress and stress environments. Post-anthesis stress was created after 14 days after anthesis. Different drought tolerance indices viz., stress susceptibility index, relative drought index, mean productivity, stress tolerance index, geometric mean productivity, yield index, yield stability index, drought resistance index were evaluated based on grain yield under stress and non-stress conditions. Thirty-one varieties recorded significantly higher grain yield under stress environments along with significant favourable most of the drought indices viz., SSI, RDI, MP, STI, YI, YSI and DRI. Only 2 genotypes, 31ESWYT-147 and C-306 produced significantly high grain yield in both stress and non-stress conditions. Further, 31ESWYT-147 also showed significant favourable values of all drought tolerance indices except GMP, whereas, C-306 showed significant favorable values only for MP, STI, YI and DRI, respectively. STI and MP showed mostly positive and meaningful genotypic and phenotypic correlation with yield in both stress and non-stress environments and with other drought tolerance indices. Thus application of both indices could be appropriate while screening the varieties for drought tolerance. However, according to both STI and MP indices, promising genotypes varied differentially for drought tolerance. MP index leads the selection towards more efficient genotypes in both stress and nonstress environment. Thus screening for drought tolerances could be made either one or both of these two indices would be more effective in bread wheat. Drought indices had low heritability and genetic gain which were comparable to yield in stress but higher than yield in non-stress condition. Hence the improvement for yield potential under drought could be achieved through direct selection in stress or screening through STI and MP indices.